Miserly developments - Jo Thori Lind; Karl Ove Moene (University of Oslo, Department of Economics, 2008)
In many countries extreme poverty is unnecessary. Yet it persists. We propose a simple index, denoted the Miser index, to measure the extent to which societies have poverty in the midst of affluence. It builds on the generalized Lorenz curve, but can also be seen as a measure of polarization between the rich and the poor. We calculate the index for a number of developing and emerging economies and rank them according to their revealed miserliness. We also identify important correlates of the Miser index. Countries that score high on the index tend to be socially fractionalized, bureaucratically inefficient, and politically corrupt. They provide their citizens with a low level of health care and education. Democracy and high growth rates do not moderate miserliness. Finally, considering the world as a single entity, we find a dramatic rise in global miserliness over the last 30 years.
Keywords: D31; D63; F35; I32; O15; 330; Miser index; poverty; affluence; inequality; development; Armut; Indexberechnung; Lorenz-Kurve; Einkommensverteilung; Entwicklung; Welt